Since MN is the midsegment, then the proportion of the side is equal to 1/2. Thus the equation for finding x is the following equation.
![(2x+3)/(9x-44)=(1)/(2)](https://img.qammunity.org/2023/formulas/mathematics/college/1r9as74jqu5ppgymhxnr4pgyk0qodvreez.png)
Thus, to solve for the value of x, multiply both sides of the equation by 2(9x-44). This will eliminate the denominators.
![2(2x+3)=9x-44](https://img.qammunity.org/2023/formulas/mathematics/college/hzryd4sixhegg2fgbsd1na0r5t4pl3ybd1.png)
Simplify both sides of the equation.
![4x+6=9x-44](https://img.qammunity.org/2023/formulas/mathematics/college/g0qpjjohav2exrvrn52orf4lbggszyiffo.png)
Isolate the variables on one side of the equation by subtracting 4x and adding 44 to both sides of the equation.
![\begin{gathered} 6+44=9x-4x \\ 50=5x \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/hupqmqw2lt7jy38evcj7n63ww82i8g8ucy.png)
To obtain the value of x, divide both sides of the equation by 5.
![\begin{gathered} (50)/(5)=(5x)/(5) \\ 10=x \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/vn5y8tuxjrzcdaters1auieexvbjeiefer.png)
Thus, the value of x is 10.
To solve for MN, substitute the value of x, which is 10, into the expression 2x+3 and then simplify.
![\begin{gathered} MN=2(10)+3 \\ MN=20+3 \\ MN=23 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/okpngrqqvbhdw1cuhln00xqagcjj7k0a1q.png)
To solve for AB, substitute the value of x, which is 10, into the expression 9x-44 and then simplify.
![\begin{gathered} AB=9(10)-44 \\ AB=90-44 \\ AB=46 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/glxvq6b2w8l8zsl91pqrqcrobrjqdbt019.png)
Notice that AB is twice the measure of MN.
Therefore the answers in the blanks should be:
Equation: 2(2x+3)=9x-44
![\begin{gathered} x=10 \\ MN=23 \\ AB=46 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/o8qyinxiq18tw721wcmv5m09r5as4pfs37.png)